Régi és új tűnődések a továbblépésről kilencven évvel a „Magunk revíziója” után - PÜSÖK, Sarolta (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2022)
Old and New Reflections on the Way Forward from the Crisis Ninety Years after the Revision of Ourselves. The topic of this paper is in line with the conference, which aims to bring together responses to crisis situations. The adjectives “old and new” in the title suggest that the impulses to move forward presented in the article come from different periods and that the questioning spans several eras. The point of departure and the basic text is Sándor Makkai’s 1931 book, Magunk revíziója (The Revision of Ourselves), followed in chronological order by Sándor Karácsony’s Ocsúdó magyarság (Awakening Hungarians), first published in 1942, and, finally, Eva Edith Eger’s book Decision, which was a bestseller for a few years. The first two authors, a Reformed theologian and a professor of pedagogy, seek a way out for Hungarians struggling with the crisis of minority fate and a mutilated country, while the third one, a Hungarian-born American psychologist who survived Auschwitz, uses the example of herself and her patients to show the universal possibility of moving on. Old and new reflections converge in the fact that when we examine the events of the past, it only makes sense to look in the mirror, to acknowledge and admit our own mistakes and errors because this gives us a chance to eliminate them, to overcome harmful habits. The past can be a deceptive mirage, and it can also enslave the retrospective, so it is worth considering the wise realization that we should not be enslaved by the actions of others, the movers of events independent of us, because they can pull us down like seaweed, paralyse us, plunge us into self-pity, perpetual victimhood, or the vortex of revenge. The secret of moving forward is to look to the future after self-examination, to seek the near and distant goals to which every small step, every task done with good cheer brings the pure-hearted, morally strengthened man – reconciled to God and man – closer. The survivors and those who move on are people of prospectivity, of diligent future building, rather than of a barren retrospective.